TECHNOLOGY ACCEPTANCE MODEL UNTUK PENGGUNAAN E_LEARNING DI UNIVERSITAS NUSA NIPA MAUMERE - Maria Florentina Rumba; , Febriyanti A Wara; Theresia W Mado (Universitas Nusa Cendana, 2020)
The application of information technology in a tertiary institution is seen as very important, in addition to being able to compete, the main objective is to support teaching and learning activities at the tertiary institution. Nusa Nipa University is one of the private universities that has implemented information technology, namely E_Campuz with one of the features contained in E_Campuz which is E_Learning. One of the characteristics of E_Learning is sharing of learning and information in this case allowing lecturers to share information related to lectures such as announcements, lecture assignments, discussions, lecture material, class agendas, etc., which can be seen or can be downloaded by students as learning material or as a discussion. The Technology Acceptance Model (TAM) developed by Davis (1989) is a successful and highly acceptable model for predicting acceptance of a newly applied technology where behavior using information technology begins with a perception of benefit (perceived of usefulness), perception of ease use information technology (ease of use), which influences attitudes toward use, as well as behavioral intentions. This research was conducted at the University of Nusa Nipa, by distributing questionnaires to 100 samples taken randomly in 18 Study Programs at UNIPA. This study aims to determine the factors - technology acceptance model (TAM), influence behavioral intentions of the use of elearning services.